Serum progranulin as an independent marker of liver fibrosis in patients with biopsy-proven nonalcoholic fatty liver disease - (:unkn) unknown (HINDAWI LTD, 2011)
Background: Elevated progranulin levels are associated with visceral obesity, elevated plasma glucose, and dyslipidemia. Progranulin has not been previously investigated as a biomarker of nonalcoholic fatty liver disease (NAFLD). We sought to determine whether serum progranulin levels are altered in patients with biopsy-proven NAFLD and if they are associated with their clinical, biochemical, and histological characteristics. Subjects and methods: We measured serum progranulin levels in 95 patients with biopsy-proven NAFLD and 80 age-and sex-matched controls. The potential associations between progranulin and the characteristics of NAFLD patients were examined by multiple linear regression analysis. Results: Serum progranulin levels were significantly higher in NAFLD patients (34 +/- 13 ng/mL) than in controls (28 +/- 7 ng/mL, P < 0.001). In NAFLD patients, serum progranulin levels were associated with lipid levels and the degree of hepatic fibrosis. After adjustment for potential confounders, serum progranulin remained an independent predictor of the degree of hepatic fibrosis in NAFLD patients (beta = 0.392; t = 2.226, P < 0.01). Conclusions: Compared with controls, NAFLD patients have higher serum progranulin concentrations, which are closely associated with lipid values and the extent of hepatic fibrosis.
Keywords: Progranulin; nonalcoholic fatty liver disease; enzyme-linked immunosorbent assay; hepatic fibrosis; GRANULIN-EPITHELIN PRECURSOR; METABOLIC SYNDROME; GROWTH-FACTOR; STEATOHEPATITIS; BIOMARKERS; ACROGRANIN; TOOLS